2015
DOI: 10.1186/s12889-015-1730-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of low HIV testing frequency and high-risk behaviour among men who have sex with men and transgender women in Lima, Peru

Abstract: BackgroundIncreased HIV testing frequency among high-risk populations such as men who have sex with men (MSM) and male-to-female transgender women (TW) can lead to earlier treatment and potentially reduce HIV transmission.MethodsWe analyzed baseline survey data from 718 high-risk, young (median age 29 [interquartile range 23–35]) MSM/TW enrolled in a community-based HIV prevention trial between 2008–2009. Participants were recruited from 24 neighborhoods in and around Lima, Peru. We assessed HIV testing freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
2
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 23 publications
5
41
2
3
Order By: Relevance
“…First, the proportion of recent condomless anal intercourse reported in this sample is not necessarily reflective of that among the larger population of MSM and TW in Peru since more than 5 episodes of condomless anal intercourse in the last 6 months was one of the seven possible eligibility criteria items and 74% of the participants reported this criterion at enrollment. However levels of condomless anal intercourse as high as 60-79% have commonly been reported in samples of Peruvian MSM and TW (Maguiña et al, 2013; Deiss et al, 2013b; Lee et al, 2015). Although this study’s eligibility criteria limits generalizability of the results, these criteria were chosen to conscientiously target a population where public health interventions should be focused.…”
Section: Discussionmentioning
confidence: 97%
“…First, the proportion of recent condomless anal intercourse reported in this sample is not necessarily reflective of that among the larger population of MSM and TW in Peru since more than 5 episodes of condomless anal intercourse in the last 6 months was one of the seven possible eligibility criteria items and 74% of the participants reported this criterion at enrollment. However levels of condomless anal intercourse as high as 60-79% have commonly been reported in samples of Peruvian MSM and TW (Maguiña et al, 2013; Deiss et al, 2013b; Lee et al, 2015). Although this study’s eligibility criteria limits generalizability of the results, these criteria were chosen to conscientiously target a population where public health interventions should be focused.…”
Section: Discussionmentioning
confidence: 97%
“…Other biobehavioral risk factors for HIV infection among TW in Peru have been documented, including high prevalence of bacterial sexually transmitted infections (STIs) and HSV-2 co-infection [1214], condomless receptive anal intercourse with HIV unknown serostatus partners [15, 16], and low rates of HIV testing and serostatus awareness [3, 1719]. Gendered power dynamics, including the need for feminine gender affirmation or validation, coercive behaviors of male partners, and cultural linkages of TW with the “feminine” receptive role during intercourse often limit TW’s control over condom use during sexual encounters [2022].…”
Section: Introductionmentioning
confidence: 99%
“…[1] The Peruvian National Ministry of Health (MoH) program's guideline on periodic medical check-ups recommends quarterly visits for MSM and transgender women, with opt-in HIV testing and counseling, but few MSM and transgender women test more than once yearly. [1,13,14] A recent study showed only 6.2% of MSM and transgender women tested semi-annually in Lima. [13] Low testing frequency results in a higher proportion of HIV infected individuals who are unaware of their HIV-infection status.…”
Section: Introductionmentioning
confidence: 99%
“…[1,13,14] A recent study showed only 6.2% of MSM and transgender women tested semi-annually in Lima. [13] Low testing frequency results in a higher proportion of HIV infected individuals who are unaware of their HIV-infection status. Previous research has demonstrated that low testing frequency is correlated with low perceived HIV risk, limited access to testing services, fear of test results, unawareness of the availability of effective treatment, and perceived stigma associated with HIV and HIV testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation